THE JUDICIAL MECHANISM IN RESOLVING AIR CONSUMER DISPUTES: A CRITICAL ANALYSIS OF CHALLENGES AND SOLUTIONS IN THE IRAQI SYSTEM - Abood, Mahmood Shaker (PT ANTIS International Publisher, 2024)
This study addresses the judicial mechanisms available for resolving consumer disputes in the field of air transport in Iraq, through a critical analysis of the challenges hindering the protection of passenger rights when disputes arise with airlines. Given the rapid developments in the global air transport sector, the judiciary becomes a vital tool for ensuring justice and protecting consumer rights. However, the Iraqi judicial system faces several challenges that hinder the swift and fair achievement of justice in this field. The main challenges consumers face in air transport include high litigation costs, the complexity of legal procedures, long waiting periods in courts, and the difficulty of proving fault against airlines, especially due to the lack of complex technical evidence. Furthermore, the lack of legal awareness among passengers about their rights makes it more difficult for them to claim compensation or defend their rights in court. These problems have been exacerbated by Iraq's failure to adopt the 1999 Montreal Convention, which strengthens consumer protection in the field of international air transport. The study aims to assess these mechanisms and offer solutions to improve the efficiency of the Iraqi judicial system in line with international standards. The study is based on a review of the relevant legal provisions.